Kebijakan Pengelolaan Ruang Terbuka Hijau (RTH) Privat dan Pengelolaan Pembangunan Berkelanjutan yang Berwawasan Lingkungan di Kota Magelang - Aditya, Federika Bella; Purnaweni, Hartuti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Development efforts in Indonesia has been going in line with technological and cultural development in the life of the Indonesians. However, it creates various environmental problems so as to degrade the environment. Therefore the government issued policy on Open Green Space in both private and public areas. This research was aimed at analyzing the implementation of Private Open Green Space in Magelang City. It used descriptive qualitative research type with data accumulated through document study and interview with informant from Public Works Office, Environment Office and the society. It came out with the result that this policy has been well implemented in terms of policy accuracy, implementation accuracy, target accuracy, environment accuracy and process accuracy. It is recommended that there should be enhancement in terms of policy accuracy, implementation accuracy, target accuracy, environment accuracy, process accuracy, resources, access of private relation, support and both local offices and society’s support. Not all policies made by the government can be implemented maximally. Many factors support the success of a policy when it is implemented. Based on the results of field findings that have been done by the research progresses then generated some recommendations of what has been concluded in the conclusion. Many things should be further developed because from the other side of Green Open Space problem in Magelang city especially Green Open Public Space is good but still lack of development of Private Green Open Space in Magelang City, from that it now become big job for all parties in order to become a good plan in the future.